Efficient BitTorrent-Like Algorithms for Interactive On-Demand Multimedia Streaming over MANETs - Rodrigues, Carlo Kleber da Silva (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
Mobile ad hoc networks pose stringent challenges for the implementation of efficient interactive on-demand streaming systems. Mobile nodes are dynamically and arbitrarily located in such a manner that the interconnections between them change on a continual basis, thereby making timely content delivery hard to achieve. To tackle this issue, we propose two BitTorrent-like algorithms. As innovative aspects, we explore (i) data dispersion, indirect reciprocity, and geographical distance as criteria to select nodes to receive data, and (ii) introduce a sliding window to decide which data segments to request first. By means of simulations on distinct multimedia scenarios, the proposals are evaluated according to four performance metrics. Among the major findings, the results highlight the effectiveness of our proposals compared to a theoretical optimal content-delivery scheme. For instance, it is shown that our proposals yield average download rates which exceed over 23% of the actual needed rate. Within this context, the key contribution of this paper is to provide valuable algorithmic insights for real-world protocol designs targeted at mobile ad hoc networks. Lastly, avenues for further research are included at the end of the paper